Perlindungan Hukum terhadap Warga Negara Asing Korban Tindak Pidana Penipuan dan Penggelapan Sewa Menyewa Tanah - I Wayan Ari Subakti; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
Legal protection is all efforts to fulfill human rights and it is offered to the broad individual so that everyone can get a sense of comfort and peace in running life without a certain threat arising from other societies, thus the community does not complain about the existence of an enforcement the rules. Criminalization is a process that arises as a result of an act carried out by each individual, where it is given a binding sanction. The purpose of this research is to find out the meaning and components in deception and embezzlement and to explain the legal protection of foreign people who are victims of the crime of renting land. This research uses normative legal methods. Deception is an act based on what someone does with regard to goods. The elements of a criminal offense are to persuade another person to hand over an item. While embezzlement of goods is an act that can harm a person in order to benefit himself. The elements of embezzlement are: whoever, an item, all or the other people who are in their territory is not a crime, by fighting the law and being aware. The legal protection of foreigners against evasion and fraud in renting land is regulated in the Criminal Code article 378 of the Criminal Code